2008
DOI: 10.1536/ihj.49.565
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcomes of Rheumatic Mitral Repair Versus Replacement

Abstract: SUMMARYMitral repair is feasible for patients with degenerative or ischemic heart disease, however, the appropriateness of repair for rheumatic heart disease remains controversial. We compared our outcomes for primary isolated mitral repair versus replacement in an elderly population. From November 1997 to July 2005, mitral repair (group I) was performed in 33 patients while 59 underwent replacement (group II). Survival and risk factors were evaluated by Kaplan-Meier and Cox regression analysis. Mean age at op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…The repair group was younger than the replacement group, consistent with the findings that use of mitral repair is inversely correlated with age [6,14,21]. Acute rheumatic mitral disease is characterised by chordal elongation, leaflet prolapse, annular dilatation and consequent predominant MR in younger individuals.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The repair group was younger than the replacement group, consistent with the findings that use of mitral repair is inversely correlated with age [6,14,21]. Acute rheumatic mitral disease is characterised by chordal elongation, leaflet prolapse, annular dilatation and consequent predominant MR in younger individuals.…”
Section: Discussionsupporting
confidence: 82%
“…As a consequence, the number of pure MR cases declines with increasing age. This ongoing activity and complicated valvular pathology may make mitral repair more difficult, and associated with less favourable postoperative outcomes [21,24]. Age-related differences in rheumatic pathologies were observed in the present work and are commonly reported in other rheumatic mitral disease studies [21,25].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In young patients such as those in the present study, implantation of a bioprosthesis was associated with a high incidence of late reoperation; in contrast, the use of a mechanical prosthesis significantly decreased the need of reoperation even if a comparison is made with repair surgery of the mitral valve of rheumatic origin. 23,24 One of the most significant findings of this experience is, on the one hand, the relatively satisfactory immediate result with 30-day mortality of 5.9% for a group of patients with polyvalvular disease and organic involvement of the tricuspid valve. If the long study period and the fact that most patients were operated on many years ago and had polyvalvular disease are considered, this 30-day mortality rate is relatively acceptable.…”
Section: Bernal Et Al Combined Mitral and Tricuspid Valve Repairmentioning
confidence: 81%
“…Besides these data based on our experience, other studies of rheumatic heart disease have shown that patients with mitral valve repair (or open mitral commissurotomy) survived longer than those undergoing mitral valve replacement with any type of prosthesis. [23][24][25] With regard to valve-related reoperation, it is well known that it depends on the type of valve substitute used. In young patients such as those in the present study, implantation of a bioprosthesis was associated with a high incidence of late reoperation; in contrast, the use of a mechanical prosthesis significantly decreased the need of reoperation even if a comparison is made with repair surgery of the mitral valve of rheumatic origin.…”
Section: Bernal Et Al Combined Mitral and Tricuspid Valve Repairmentioning
confidence: 99%